Long-term strategy of Russia’s activity in the Antarctic - Lukin, V.V. (Ukrainian Antarctic Journal, 2012)
On 30 October 2010, the Government of the Russian Federation has adopted the “Strategy for the development of the Russian Federation’s activities in the Antarctic for the period until 2020 and longer-term perspective”. The aims and goals of the Strategy are considered, the current level of activity of Russia in the Antarctic and existing problems are assessed and the ways of addressing them, are proposed. The main directions of activity of Russia in the South Polar area for the period under consideration include: strengthening of the positions of Russia in the Antarctic Treaty System, an assessment of role and place of the Antarctic in global climate changes, ground support of space activity of Russia using the infrastructure of the Russian Antarctic Expedition, wider use of marine biological resources of the Antarctic by the Russian fishery branch, an assessment of perspectives of potential mineral and hydrocarbon resources of the Antarctic observing all requirements of the Protocol on Environmental Protection to the Antarctic Treaty, implementation of basic and applied scientific studies of the Antarctic at the current international level, environmental protection of the region, upgrading and reconstruction of the infrastructure of the Russian Antarctic Expedition. The program measures for implementing the provisions of the Strategy and sources of their funding are defined.